(untitled) (Research, Society and Development, 2021)
Type 2 Diabetes Mellitus (Type 2 DM) is a chronic and highly prevalent disease that is considered a global epidemic. However, when properly treated, it can be well controlled and have its complications minimized. The use of digital technologies emerges as a potential instrument to help teaching about this very prevalent disease, even more in the scenario of student-centered education, more intensified in the period of the new coronavirus pandemic. This cross-sectional, descriptive study with a quantitative approach aims to develop and evaluate the usability of a digital platform as a tool for teaching medical students about drug treatment and microvascular complications in patients with type 2 diabetes. For the development of the digital platform, assumptions adapted from Echer (2005) were adopted and its usability was evaluated through the System Usability Scale (SUS) among undergraduate medical students. 45 responses were obtained. Students from different semesters participated, 93.3% having already taken the endocrinology programme. The application received a good usability evaluation, obtaining an average SUS score equal to 82.9, with a standard deviation of 13.8. In conclusion, the digital platform for teaching about the treatment and complications of type 2 Diabetes Mellitus had a good evaluation among medical students, and it can be used as an instrument for teaching this area of endocrinology in undergraduate medicine.